Gene Therapy Tools and Potential Applications - Martin Molina, Francisco (IntechOpen, 2013)
The Gene Therapy field is living exciting times after more than 20 years of poor results. Scientist and clinicians working in the gene therapy field have encountered many problems in the past that are now starting to be solved. The development of safer and more efficient gene transfer vectors and the advances on the cell therapy field have open new opportunities to tackle different diseases. The aim of this book is to bring together information about the different gene therapy tools, the clinical successes of gene therapy and the future applications.